Accuracy of single radial hemolysis test for rubella immunity when internal reference standards are used to estimate antibody levels. - Nommensen, F E (1987)
The accuracy and reproducibility of antibody levels obtained by single radial hemolysis with six internal reference sera were evaluated. The test was performed in a clinical laboratory for routine assessment of immunity to rubella infection over a period of 1 year. A linear relationship exists between the antibody titer (expressed in log dilution) and zone diameters. In 43 of 44 test runs the correlation coefficient of the standard curve was over 0.990. Prediction limits of 95% around the curve showed that on replication of the test, zone diameters could be found within less than half a doubling-dilution step. The antibody level can thus be determined more accurately by the single radial hemolysis test than in the conventional hemagglutination inhibition test. This is particularly important in assessing immunity when antibody titers are low, since the hemagglutination inhibition test is less reliable then. The use of standard sera calibrated international units would render results of different laboratories comparable and allow standardization at threshold values.